DETERMINAÇÃO DA PREVALÊNCIA DE INFECÇÃO PELO VÍRUS LINFOTRÓPICO DE CÉLULAS T HUMANAS (HTLV) TIPOS 1 E 2 POR MÉTODOS SOROLÓGICOS E MOLECULARES EM AMOSTRAS DE SANGUE DE GESTANTES - MENDES, Maria de Fátima Castro (2020)
The human T-cell lymphotropic virus (HTLV) is a retrovirus that is associated with several types of diseases: hematological, immunological, dermatological, ophthalmologic, neurological, and urologic. Breastfeeding is the main way of HTLV-1/2 transmission from mother to child. The present study aimed to investigate, through serological and molecular methods, the prevalence of HTLV-1/2 infections in pregnant women aged 15-45 years, attended at the Central Public Health Laboratory of Maranhão (LACEN-MA). A cross-sectional study was conducted with 713 pregnant women who spontaneously gave blood samples to be screened by Chemiluminescent Microparticle Immunoassay (CMIA) for the qualitative determination of anti-HTLV-1/2 antibodies, and Western blot test (WB) HTLV-1/2 for the confirmation of reactive results. The genetic material was extracted from peripheral blood mononuclear cells (PBMCs) of all 713 samples and subjected to Polymerase Chain Reaction (PCR) with specific primers specifically designed for this study. Sociodemographic and epidemiological data of the pregnant women investigated revealed that the age ranged from 15 to 43 years, with an average of 24.3 ± 6.2 years, with a predominance of the mulattos ethnic group (63.8%); 95.2% were from the metropolitan area of São Luís; 71.8% were married or in stable union; 61.7% had completed schooling equal to or superior to high school education; 53.7% reported domestic activities; 56.9% had previous pregnancies; 72.0% had a family income of 1 to 3 minimum wages, and 49.6% of the households were made up of 1 to 3 people. Regarding the risk factors for the occurrence of HTLV infection, it was observed that 55% of the partners of pregnant women sometimes used condoms; 9% of them had no fixed sexual partner; in 3.6%, the partner was an injecting drug user; 4.6% were submitted to blood transfusion, and 66.7% of women with previous pregnancies breastfed for more than six months. In blood samples serologically screened by CMIA, 05 sera were found HTLV-1/2 reactive. After confirmation by WB, it was found that 3 (0.42%) were positive for HTLV-1, while 2 presented indeterminate results. PCR amplification confirmed that the 5 CMIA reactive samples were also positive for HTLV-1 by PCR. The results of CMIA and PCR showed a prevalence of 0.7% of HTLV-1 in pregnant women in the metropolitan region of São Luís, placing the capital of Maranhao among the capital with the highest prevalence of HTLV-1 in Brazil in this population.The sum of the results points to the need of taking public policies for the prevention and control of this infection, including making it compulsory to screen HTLV-1/2 in prenatal care, adopting educational measures for the population and health professionals in the sense of counseling not breastfeeding in cases of infected mothers, and making such infection of compulsory notification.